2017
DOI: 10.1371/journal.pone.0182835
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid suppresses malignant characteristics of CD133-positive thyroid cancer stem cells and induces apoptosis

Abstract: Recently, diagnoses of radioiodine-refractory differentiated thyroid cancer (RAI-R DTC) have become more common; prognosis is poor. It has been suggested that cancer stem cells account for radiotherapy resistance. By flow cytometry, different expression percents of CD133 and OCT4 in thyroid cancer cell lines were detected. By real-time quantitative PCR, different mRNA expression of CD133, OCT4, GLUT1, thyroglobulin (TG), thyroperoxidase (TPO) and sodium iodine symporter (NIS) was analyzed; the localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Prominin 1/CD133 significantly decreased in U87MG exposed to ATRA (10 −6 M, 1-fold, p = 0.003; 10 −4 M, 1.7-fold, p = 0.000024) in comparison to non-treated cells ( Figure 1 ). This data supports the role of ATRA in the inhibition of stem cell characteristics as seen with other cancer types, e.g., thyroid [ 24 ]. As glioblastoma has a sub-population of stem cells capable of self-renewal and radiotherapy resistance, the response of prominin-1/CD133 to ATRA in U87MG may potentially serve as a GBM cell line model for targeted differentiation strategies.…”
Section: Resultssupporting
confidence: 86%
“…Prominin 1/CD133 significantly decreased in U87MG exposed to ATRA (10 −6 M, 1-fold, p = 0.003; 10 −4 M, 1.7-fold, p = 0.000024) in comparison to non-treated cells ( Figure 1 ). This data supports the role of ATRA in the inhibition of stem cell characteristics as seen with other cancer types, e.g., thyroid [ 24 ]. As glioblastoma has a sub-population of stem cells capable of self-renewal and radiotherapy resistance, the response of prominin-1/CD133 to ATRA in U87MG may potentially serve as a GBM cell line model for targeted differentiation strategies.…”
Section: Resultssupporting
confidence: 86%
“…In contrast, tretinoin, an analog of vitamin A, was first proven as a medication for acne [51], and has been used to treat APL since the 1990s [52]. Recent studies also reported its potential role on suppressing other cancers such as lung cancer [53] and thyroid cancer [54]. In this regard, our in vitro cell line results also revealed that tretinoin had synergetic effects with lower concentrations of sunitinib (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The treatment of APL with ATRA leads to the dissociation of these repressor complexes and triggers the gene expression of the RARA-responsive genes [ 59 ]. The ATRA treatment was shown to sensitize different tumor types to the conventional treatment [ 56 , 58 , 60 , 61 ] and inhibit CSC populations [ 57 , 58 , 62 ]. In PCa, ATRA was shown to inhibit the proliferation of AR-negative cells by activating cyclin-dependent kinase 5 (Cdk5) and p27 expression [ 63 ].…”
Section: Aldh1a1mentioning
confidence: 99%